The lift-off stage of plasma focus discharges - Bruzzone, Horacio Abel (2007)
A simple model describing th lift-off of the current sheet in the initial satge of a plasma focus (PF) discharges is presented. The model results are supported by measurement performed on a low energy PF device and also with other experimental results found in yhe literature. Tha ideas used in the model have sufficient general validity so that they can be applied to essentially all existing PF devices.